Evaluation of environmental bacterial contamination and procedures to control cross infection in a sample of Italian dental surgeries. Issue 11 (1st November 2000) - Monarca, Silvano; Grottolo, Mario; Renzi, Daniela; Paganelli, Corrado; Sapelli, Pierluigi; Zerbini, Ilaria; Nardi, Giuseppe
Abstract : OBJECTIVES: To perform a pilot study on bacterial contamination in some dental surgeries (n=51) in a local health unit in Brescia (Lombardy Region, Italy) and to evaluate the procedures to control cross infection used by the personnel to reduce the risk of infection in dental practice. METHODS: A survey was carried out by interviewing 133 dental personnel with a questionnaire on the procedures used to control infection. The autoclaves, chemical baths (chemiclaves), and ovens present in the surgeries were tested for sterilisation efficiency with a spore test, and already packed and sterilised instruments were randomly sampled and tested for sterility. Microbial contamination of air, surface, and dental unit water samples were also studied. RESULTS: The dental personnel did not generally follow the principal procedures for infection control: 30% of personnel were not vaccinated against hepatitis B virus, infected instruments were often not decontaminated, periodic checks of autoclave efficiency were lacking, and the knowledge of disinfection mechanisms and procedures was incomplete. High bacteriological contamination of water at dental surgeries was often found and total bacteriological counts in air samples were high. Surface studies showed widespread bacterial contamination. CONCLUSIONS: On the basis of these results, an educational programme for the prevention of infective hazards has been prepared and carried out. The results of this pilot study will be used for planning a national survey.